2012
DOI: 10.1002/aic.13863
|View full text |Cite
|
Sign up to set email alerts
|

Finite volume method for falling liquid films carrying monodisperse spheres in Newtonian regime

Abstract: A finite volume method is proposed to study the dynamics of unsteady, falling liquid films carrying monodisperse spheres in Newtonian regime under the action of gravity. The Navier–Stokes equations were rewritten to implement a numerical scheme with interface capturing capability, able to compute discontinuities in the solid volumetric concentration and free surface flows. The interface capturing property is checked with simple benchmarks, showing that experimental data for a vertical settler and the dynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
(179 reference statements)
0
5
0
Order By: Relevance
“…Although this regime was primarily distinguished by the propagation of bumps and ripples along the free surface, it had nothing to do with free-surface instabilities (roll waves), which are observed at much higher Reynolds numbers. 17 Here we focus on Run I, but the same kind of behavior was observed for other runs. A few seconds after the release (typically t > 3 − 5 s for a mass of ∼8 kg), we observed that the free surface deformed and became bumpy.…”
Section: Fracture Regimementioning
confidence: 87%
“…Although this regime was primarily distinguished by the propagation of bumps and ripples along the free surface, it had nothing to do with free-surface instabilities (roll waves), which are observed at much higher Reynolds numbers. 17 Here we focus on Run I, but the same kind of behavior was observed for other runs. A few seconds after the release (typically t > 3 − 5 s for a mass of ∼8 kg), we observed that the free surface deformed and became bumpy.…”
Section: Fracture Regimementioning
confidence: 87%
“…Another formulation can be devised for ASMM in terms of the velocity of the center‐of‐volume or the volumetric flux , trueu MathClass-rel= αptruevp MathClass-bin+ αqtruevq. To do so, it is necessary to find a relationship between the velocity of center‐of‐mass and this new velocity . The desired relationship is shown in Eqn.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…A brief summary of the VOF method is given following the description given by Bohorquez . The continuity equation is given by ρt+·(ρv)=0 in which the mixture density is given by ρ=ρ1α+ρ2(1α) …”
Section: Numerical Schemementioning
confidence: 99%
“…The tensor τ(2) represents the momentum diffusion due to the relative motion between the two‐phases. It is therefore called the “diffusion stress term.” (The details about the modeling of this term can be found in Bohorquez.) To model the effect of the surface tension the term γκα is added to the right‐hand side (RHS) of the momentum balance equation as suggested Brackbill et al γ is the interfacial tension and κ the local surface curvature.…”
Section: Numerical Schemementioning
confidence: 99%
See 1 more Smart Citation